The expression of PKM1 and PKM2 in developing, benign, and cancerous prostatic tissues - Li, Lin; Cheng, Siyuan; Yeh, Yunshin; Shi, Yingli; Henderson, Nikayla; Price, David; Gu, Xin; Yu, Xiuping (Frontiers in Oncology, 2024)
Neuroendocrine prostate cancer (NEPCa) is the most aggressive type of prostate cancer (PCa). However, energy metabolism, one of the hallmarks of cancer, in NEPCa has not been well studied. Pyruvate kinase M (PKM), which catalyzes the final step of glycolysis, has two main splicing isoforms, PKM1 and PKM2. In this study, using immunohistochemistry, immunofluorescence staining, and bioinformatic analysis, we examined the expression of PKM1 and PKM2 in mouse and human prostatic tissues, including developing, benign, and cancerous prostate. We found that PKM2 was the predominant isoform expressed throughout prostate development and PCa progression, with slightly reduced expression in murine NEPCa. PKM1 was mostly expressed in stromal cells but low-level PKM1 was also detected in prostate basal epithelial cells. Its expression was absent in the majority of prostate adenocarcinoma (AdPCa) specimens but present in a subset of NEPCa. Additionally, we evaluated the mRNA levels of ten PKM isoforms that express exon 9 (PKM1-like) or exon 10 (PKM2-like). Some of these isoforms showed notable expression levels in PCa cell lines and human PCa specimens. These findings lay the groundwork for understanding the metabolic changes in different PCa subtypes.